The American stamp postal iconography, democratic citizenship, and consumerism in the United States - Goldblatt, Laura; Handler, Richard 1950- (Columbia University Press, 2023)
"The postage stamp of the United States is a window into the ideology of American citizenship. Stamps differ from other repositories of nationalist messaging such as monuments, museums and textbooks. They are centrally controlled (by the post office), yet they change rapidly-more than three thousand different stamps have been deployed since the middle of the nineteenth century. The ubiquity of stamps in national life-and the fact that they change regularly yet remain controlled by a remarkably stable national agency-have made them a site where some of the deepest principles of U.S. national citizenship have been fixed, developed, deployed and challenged. The American Stamp is a study of the iconography and material history explores how the postage stamp has been a staging ground for a long-term debate concerning two views of U.S. citizenship, one centered on the freedoms afforded by democracy and the other on the freedoms afforded by consumerism.
Includes bibliographical references and index
Keywords: Geschichte 1847-2000; Briefmarke; USA; Postage stamps / United States; Commemorative postage stamps / United States; National characteristics, American; Timbres-poste commémoratifs / États-Unis; Commemorative postage stamps; Postage stamps; United States